Mapeamento térmico urbano de cidades semiáridas de médio porte: uma análise aplicada à realidade de Sobral, como subsídio ao planejamento climático urbano local - Brasileiro, Francisca Mairla Gomes (2023)
The present research sought to evaluate the urban climate of the city of Sobral in order to diagnose the characteristics of the thermal environment of the city and propose mitigating actions that contribute to the urban climate planning of the city. To this end, the methodology used was based on a literature review and the application of models for urban climate classification, namely, urban climate mapping (UCMap) and local climate zones (LCZ). Associated with these methodologies, mobile transects were applied in different types of time, dry and rainy period, to measure the air temperature conditions in the various features of the urban landscape and verify the accuracy of the mappings in the field. As a result, it was found that the city of Sobral has a specific urban climate, with the generation of climatic phenomena, especially those related to the thermal field. The construction of the UCMap was related to the production of ten base layers and two synthesis maps that revealed the climatic and urban conditions of the city, in addition to emphasizing the distribution of the termal load and the dynamic potential of the city. From the synthesis maps, the climate analysis map (UC-AnMap) was elaborated, revealing the disposition of eight climatopes in the city's landscape, of these, three effectively contribute to the increase in local temperature (climatops 6 to 8), with a covered area of 19.6%. It is noted that 2.2% of these features are associated with the phenomenon of heat islands, as they have a very high thermal load. Regarding the mapping of LCZs, it is observed that Sobral has 12 LCZs, 6 of which are related to the types built and 6 relating to the types of land covers. Among the LCZs, there is a predominance of LCZ 3, since the city has large zones associated with horizontal features of high compaction. From the identification of the LCZ it was possible to better characterize the urban landscape and climatic aspects of Sobral. Based on this information, a comparison was made with the microclimatic data of air temperature, showing for the climatopes low temperatures in classes close to 1 and high temperatures in classes close to 8. In the LCZs, the temperatures showed greater variation and lower correlation due to their zonal character, however, the classes of the constructed types prevailed with the higher temperatures. In general, it was observed that the zones of higher and lowest air temperature are related to what was visualized in the classifications. Based on the evaluation of the thermal data of Sobral, the proposal of mitigating measures and actions was forwarded. Thus, a planning recommendation map (UC- ReMap) was elaborated, where the level of thermal impact is indicated and the actions that can be implemented in the different urban planning zones (UCPZ). Regarding this aspect, it was observed for Sobral the urgency of the application of intervention measures in UCPZ 4, given its potential for the generation of climatic phenomena and intense thermal discomfort. Therefore, it is concluded that the work enabled a robust evaluation of the termal environment of the city of Sobral and contributed to the identification of critical areas in need of short-term urban and climate interventions.